2011
DOI: 10.1523/jneurosci.1543-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal and Monoaminergic Contributions to Stop-Signal Task Performance in Rats

Abstract: Defining the neural and neurochemical substrates of response inhibition is of crucial importance for the study and treatment of pathologies characterized by impulsivity such as attention-deficit/hyperactivity disorder and addiction. The stop-signal task (SST) is one of the most popular paradigms used to study the speed and efficacy of inhibitory processes in humans and other animals. Here we investigated the effect of temporarily inactivating different prefrontal subregions in the rat by means of muscimol micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
125
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(142 citation statements)
references
References 98 publications
14
125
2
1
Order By: Relevance
“…Our data were consistent with findings in people and previous rat models (Aron et al, 2003;Bari et al, 2009;Bari et al, 2011;Broos et al, 2012;Chamberlain et al, 2006;Eagle et al, 2007;Tannock et al, 1989) and showed that the general ability of these drugs to enhance stopping in the SSRTT extended to mice. The effects of both drugs were dose dependent with the inhibition-promoting effects being lost at higher doses, presumably as a result of a relative reduction in pharmacological selectivity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data were consistent with findings in people and previous rat models (Aron et al, 2003;Bari et al, 2009;Bari et al, 2011;Broos et al, 2012;Chamberlain et al, 2006;Eagle et al, 2007;Tannock et al, 1989) and showed that the general ability of these drugs to enhance stopping in the SSRTT extended to mice. The effects of both drugs were dose dependent with the inhibition-promoting effects being lost at higher doses, presumably as a result of a relative reduction in pharmacological selectivity.…”
Section: Discussionsupporting
confidence: 93%
“…The SSRTT measures the ability to stop or cancel a motor action once started in response to a 'stop-signal' and detects inhibitory deficits in pathological conditions such as ADHD (Alderson et al, 2007;Robbins, 2007). Rats can learn this task and show similar speeds of reaction and sensitivity to task manipulations as people; they also show a similar pattern of effects to drug challenges, most notably recapitulating the inhibitionenhancing properties of the clinically effective drugs methylphenidate and atomoxetine (Bari et al, 2009(Bari et al, , 2011Broos et al, 2012;Eagle et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that mPFC is both affected by PNE and is critical for normal performance on stop-signal paradigms (Bari et al, 2011;Schneider et al, 2011;Zhu et al, 2012). Here, we show that PNE makes rats more impulsive and attenuates neural selectivity related to the direction of the response and monitoring of conflict in mPFC.…”
Section: Introductionsupporting
confidence: 54%
“…This is surprising considering the number of studies that have implicated mPFC in inhibitory control. For instance, perturbation of the rat prelimbic prefrontal cortex reveals stop-signal reaction time deficits (Bari et al, 2011) and increased premature responses during performance of reaction time tasks (Pezze et al, 2014;Risterucci et al, 2003). However, similar approaches have yielded conflicting results (Christakou et al, 2001;Eagle et al, 2008;Eagle and Robbins, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For example, whereas yohimbine-induced impulsivity involves activation of specific signaling cascades in the lOFC (Sun et al, 2010), lesions of the infralimbic region of PFC, not lOFC, have been reported to increase impulsive responding in the face of increasing ITIs on the 5CSRTT (Chudasama et al, 2003). Similarly, behavioral inhibition on the SSRTT may be more dependent on dorsal medial PFC and dorsal striatal activity (Bari et al, 2011;Eagle and Robbins, 2003a;Eagle et al, 2011), whereas choice behavior on the delay-discounting task may be more dependent on a circuit involving the lOFC and ventral striatum (Bezzina et al, 2008;Bezzina et al, 2007;Mobini et al, 2002). Whatever the mechanism, an increase in the likelihood of making impulsive decisions, particularly for immediate 'gratification', could certainly put individuals at a higher risk for developing addictive disorders.…”
Section: Discussionmentioning
confidence: 99%